Impact of microphysics parameterization schemes in simulation of vardah cyclone using the advanced mesoscale weather research and forecasting model - Janardhan Saikumar, P; Ramashri, T (International Journal of Engineering and Technology, 2018)
The very severe Tropical Cyclone Vardah caused huge damage to property and life in south India during December 2016. The sensitivity of numerical simulations of the very severe tropical cyclone Vardah to different physics parameterization schemes is carried out to determine the best microphysics and cumulus physics parameterization schemes. The WRF Numerical weather prediction model configured with two nested domains. The horizontal resolution of domain-1is 27 km and domain-2 is 9 km. The tropical cyclone Vardah simulated track results were compared with the best track data given by the Indian Meteorological Department (IMD). WRF model Simulations were carried out using different microphysics (mp) parameterization schemes by fixing convective cumulus physics (cu) option to Grell-3D ensemble scheme and boundary layer option to updated Yonsei University scheme. The Vardah Cyclone track well simulated using WRF Single Moment-3 (WSM3) microphysics scheme in combination with G3D cumulus physics scheme. The cumulus physics and microphysics parameterization schemes influence the cyclone track prediction skill.Â Â
Keywords: Vardah; ARW Model; Physics Parameterizations; Cyclone Track; Track Error